2014
DOI: 10.1177/0021998314536070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of specimen history on structure and in-plane permeability of woven fabrics

Abstract: Before being processed into composites, reinforcement fabrics may undergo repeated involuntary deformation, the complete sequence of which is here referred to as speci men history. To mimic its effect, fabric specimens were subjected to sequences of defined shear operations. For single fabric layers with unconstrained thickness, quantitative evaluation of photographic image data indicated that repeated shear deformation results in a residual increase in inter-yarn gap width. This translates into an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Fundamental characterisation of the adhesive properties of LM microcapsules onto fabric substrates is vital to understand their potential applications in fabric care via maximising their retention onto target fabrics. A smooth and flat PET film as a model substrate may help to avoid any typical steric effect and physical interference due to crimp and coarse woven fabrics [ 45 ]. The retention performance (RP) of LM microcapsules onto PET films as a function of the hydrodynamic shear stress ( τ ) and the Reynolds number (Re) is shown in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Fundamental characterisation of the adhesive properties of LM microcapsules onto fabric substrates is vital to understand their potential applications in fabric care via maximising their retention onto target fabrics. A smooth and flat PET film as a model substrate may help to avoid any typical steric effect and physical interference due to crimp and coarse woven fabrics [ 45 ]. The retention performance (RP) of LM microcapsules onto PET films as a function of the hydrodynamic shear stress ( τ ) and the Reynolds number (Re) is shown in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown that technical textiles do exhibit a significant amount of variation [20][21][22][23] and that this variation does influence the textile's permeability. 24,25 Hence, this paper examines the influence that geometric variations have on the textile's permeability. This is an aspect that is otherwise very difficult to control and study experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to those variables, handling of textiles can change the geometry of the reinforcement and hence affect variability. 23 Mechanical testing showed a significant difference in behaviour of woven laminates with no layer shift and random layer shift. The latter demonstrated almost linear behaviour with a small deviation from this after 0.7% strain while the laminates with no layer shift exhibited significantly non-linear behaviour with a well defined kink point at about 0.9% strain.…”
Section: Discussionmentioning
confidence: 96%
“…Analysis of the reinforcement geometry at the surface of the composite panels showed that systematic variations are lower than in the dry reinforcement, up to 0.7 mm, but no data were obtained on stochastic variation due to the poor quality imaging obtained from the composites. According to Endruweit et al 23 repetitive specimen handling may decrease the geometrical variability. However, such handling is reduced in the RTM process because the reinforcement mobility is restricted by inter-layer friction.…”
Section: Geometry Characterisationmentioning
confidence: 99%